2020
DOI: 10.36941/jesr-2020-0057
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Rational Behavioral Emotive Program in Reducing Test Anxiety among University Students with High Academic Achievement

Abstract: The present study aims to identify the effectiveness of a rational behavioral emotive program in reducing test anxiety among university students with high academic achievement in Riyadh. The author adopted the quasi-experimental approach. The sample comprised (26) students with high academic achievement who were encountering test anxiety at Princess Nourah bint Abdulrahman University (PNU) in Riyadh. The participants were divided into two groups: An experimental group of (13) students and a control group of (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
0
0
Order By: Relevance
“…The findings consistent with study the relationship between knowledge and demographic characteristics that show high significant relationship between late adults' knowledge about social frailty and age, gender, job title, life style and do exercise regularly; this result is agreed in the study is carried-out among high-school students results showed that there are statistically significant differences in stuttering and social anxiety between the experimental and control groups (26) .…”
Section: Discussionsupporting
confidence: 85%
“…The findings consistent with study the relationship between knowledge and demographic characteristics that show high significant relationship between late adults' knowledge about social frailty and age, gender, job title, life style and do exercise regularly; this result is agreed in the study is carried-out among high-school students results showed that there are statistically significant differences in stuttering and social anxiety between the experimental and control groups (26) .…”
Section: Discussionsupporting
confidence: 85%